Building capacity for information and communication technology use in global health research and training in China: a qualitative study among Chinese health sciences faculty members - Jie Wang; Abu S. Abdullah; Zhenyu Ma; Hua Fu; Kaiyong Huang; Hongping Yu; Jiaji Wang; Le Cai; Huimin He; Jian Xiao; Lisa Quintiliani; Robert H. Friedman; et al. (BMC, 2017)
Abstract Background The demand to use information and communications technology (ICT) in education and research has grown fast among researchers and educators working in global health. However, access to ICT resources and the capacity to use them in global health research remains limited among developing country faculty members. In order to address the global health needs and to design an ICT-related training course, we herein explored the Chinese health science faculty members' perceptions and learning needs for ICT use. Methods Nine focus groups discussions (FGDs) were conducted during December 2015 to March 2016, involving 63 faculty members working in areas of health sciences from six universities in China. All FGDs were audio recorded and analysed thematically. Results The findings suggest that the understandings of ICT were not clear among many researchers; some thought that the concept of ICT was too wide and ambiguous. Most participants were able to cite examples of ICT application in their research and teaching activities. Positive attitudes and high needs of ICT use and training were common among most participants. Recommendations for ICT training included customised training programmes focusing on a specific specialty, maintaining a balance between theories and practical applications, more emphasis on the application of ICT, and skills in finding the required information from the bulk information available in the internet. Suggestions regarding the format and offering of training included short training programmes, flexible timing, lectures with practicum opportunities, and free of charge or with very minimal cost to the participants. Two participants suggested the linking of ICT-related training courses with faculty members' year-end assessment and promotion. Conclusions This study among health sciences faculty members in China demonstrated a high level of need and interest in learning about ICT use in research and training. The results have important implications for the design and implementation of ICT-related educational programmes in China and other developing countries.